Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean - Wittmann, Karl J. (Zootaxa, 2020)
Detection of previously unknown, dimorphic setal patterns on the carpus of the fifth thoracic endopod in types of Parvimysis bahamensis Brattegard, 1969, representing the type species of the genus Parvimysis Brattegard, 1969, required revision of this genus together with taxonomic verification of materials previously assigned to this species from all around the Caribbean. Study of this material together with new samples from marine waters of Curaçao led to the detection of five new species. Four of these species have a dimorphic carpus of the fifth endopod and are here described as P. pricei sp. nov., P. laminata sp. nov., P. brattegardi sp. nov., and P. ornata sp. nov. One species with non-dimorphic setal patterns is described as P. nuda sp. nov. Two species groups are defined based on structural differences of the carapace, mandibular and maxillary palpus, oostegites and telson: the P. bahamensis group with six species from marine waters of the Caribbean and an additional one from brackish-freshwaters of Surinam, versus the P. amazonica group with seven species from freshwaters of Amazonia. A key to the 14 species currently known from the genus Parvimysis is provided.